Динаміка уявлень населення України про суб’єктивно-нормальний дохід - Бова, А. (Социология: теория, методы, маркетинг, 2009)
The data of monitoring of the Ukrainian population’s opinions testify to the increase of the level of their wages and incomes. At the same time, these incomes on the average de minimis exceed the (understated) size of the living wage set by the state. The results of the public opinion surveys conducted by the Institute of sociology, NAN of Ukraine, show that according to Ukrainians’ beliefs an income which is needed for normal life must four times exceed the per-income (that corresponds to the level of poor family and does not provide even the half of the living wage). During 1998–2008 a per income grew in 4,8 times, while the subjectively-normal income — in 3,5 times, and the income indicating the family as a poor one — in 4,1 times. Material income and claims of population began swiftly to increase since 2002. The analysis gives grounds to assert the increase of both the real and the subjectively-normal incomes during 2007–2008.